PROTECTION OF CHILDREN VICTIMS OF VIOLENCE IN THE FAMILY PERSPECTIVE OF ISLAMIC FAMILY LAW AND POSITIVE LAW (Study at the Lampung Province Child Protection Institute, the Damar Lampung Child Advocacy Institute and the Regional Technical Implementation Uni - Sulastri; Sovi Septania (Bajang Institute, 2022)
A child protection refers to any efforts aimed at ensuring and protecting children and their rights so that they can grow, develop, and contribute to their full potential while remaining safe from violence and discrimination. Child protection is handled by a number of organizations, namely the Child Protection Institute, Lampung, the child advocacy institution of Damar Lampung, and the Technical Implementation Unit for the Protection of Women and Children, Lampung. Despite the fact that these three organizations exist and operate, family violence against children continues to rise. The conclusions are (1) Threats, compulsion, fear, opportunity, power relations, economy, patriarchy, lack of morals, inability to control themselves, retribution, and lack of attention from biological moms to children's behavior are all prevalent reasons of violence against children in three institutions. The difference is that there is a sexual disorder, husband is afraid of his old wife, lack of communication between children and mother, home environment, access to meet is cut off, mother dies, revenge, persuasion, habit of having sexual relations. Study/add insight into Islam and practice it, learn and practice good morals, hang out a lot with pious and pious people, exercise self-control, psychological approach, intensity of education are some of the solutions to decrease them. (2) The types of services provided by child protection institutions, child advocacy institutions, and the Technical Implementation Unit for the Protection of Women and Children (UPTD PPA) are similar in terms of type of service, legal basis, service principle, Standard Operating Procedure (SOP) for mentoring, code of ethics, and ethics, but each has its own characteristics in terms of technical assistance, human resources, funding sources, and facilities. (3) The hadhanah concept (care, care, and education) is reflected in the perspective of Islamic family law and positive law on child protection carried out by three institutions, referring to Law No. 4 of 1979 concerning Child Welfare, Law No. 35 of 2014 on Child Protection, Law No. 11 of 2012 on Child Criminal Justice, Law No. 23 of 2004 on Marriage, Compilation of Islamic Law leading to District Courts (Criminal), Religious Courts (Civil), and Mediation.